2016
DOI: 10.1080/09712119.2015.1124334
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the species of origin in commercial sausages in South Korea

Abstract: This study aimed to develop a rapid and reliable method for identifying the species origin of the meat in commercial sausages using amplification patterns for mitochondrial DNA (mtDNA). Forty commercial sausages were purchased from retail markets and subjected to mtDNA analysis. Two mtDNA markers were used for amplifying the meat source DNA. To optimize the PCR conditions, gradient PCR reactions were carried out to determine the primer annealing temperatures, and real-time PCR was done to check the minimal amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…However, the mixture in their investigation consisted of pork and sheep raw meat, which could lead to more efficient amplification of sheep DNA than in our study. Previous investigations have reported the efficient use of different restriction enzymes for differentiation of different animal species on the basis of the mitochondrial cytochrome b gene (Farag et al 2015;Han et al 2016), the COI gene (Haider et al 2012;Spychaj et al 2016), and 12s RNA (Girish et al 2007;Chen et al 2012). However, most of these investigations were conducted either on mixtures of raw meat, or on meat products which were not submitted to technological operations of smoking, salting, changes of pH etc., where much of the DNA is degraded, leading to a scenario in which the DNA of one species can be amplified more efficiently than that of the other.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mixture in their investigation consisted of pork and sheep raw meat, which could lead to more efficient amplification of sheep DNA than in our study. Previous investigations have reported the efficient use of different restriction enzymes for differentiation of different animal species on the basis of the mitochondrial cytochrome b gene (Farag et al 2015;Han et al 2016), the COI gene (Haider et al 2012;Spychaj et al 2016), and 12s RNA (Girish et al 2007;Chen et al 2012). However, most of these investigations were conducted either on mixtures of raw meat, or on meat products which were not submitted to technological operations of smoking, salting, changes of pH etc., where much of the DNA is degraded, leading to a scenario in which the DNA of one species can be amplified more efficiently than that of the other.…”
Section: Resultsmentioning
confidence: 99%
“…Various intercalating dye-based qPCR techniques for analyzing porcine DNA in raw and processed food products have been successfully developed. Using SYBR ® Green dye, Han et al [22] successfully identified pig meat in commercial sausages. In another study, SYBR ® Green I-based qPCR assay was able to detect pork in processed food [23].…”
Section: Introductionmentioning
confidence: 99%
“…Además, cumplen un papel importante en la emulsión cárnica, apariencia deseable, exquisitez, aceptabilidad de la textura y una sensación de saciedad. Por lo tanto, la información declarada por el fabricante en la etiqueta del producto es importante, para que el consumidor realice una elección inteligente, en razón a sus necesidades y un mejor control en la cadena de comercialización, por lo que se hace necesario contener la información sobre todos los componentes del producto, incluida la fuente de carne (Han et al 2016).…”
Section: Introductionunclassified